Empatia in orchestra (Materiali di Estetica. Terza serie, 2025)
This contribution tries to highlight the complexity of the relationships that exist between the conductor and the orchestral players, in light of the different personalities that are present in an ensemble of instrumentalists. The conductor has to deal with an incredibly varied “musical instrument” such as an orchestra, where individuals characterized by sometimes very dissimilar backgrounds and sensibilities must be harmonized and coordinated. To accomplish this task, which requires artistic temperament but also psychological finesse, the conductor must relate to his collaborators with authority combined with a singular mixture of empathic ability, intuition and creativity.
Keywords: orchestra; conductor; leadership; music